2010
DOI: 10.1128/aac.00762-10
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Ciprofloxacin Resistance in Pseudomonas aeruginosa Involves Multiple Response Stages and Multiple Proteins

Abstract: Microbes have developed resistance to nearly every antibiotic, yet the steps leading to drug resistance remain unclear. Here we report a multistage process by which Pseudomonas aeruginosa acquires drug resistance following exposure to ciprofloxacin at levels ranging from 0.5؋ to 8؋ the initial MIC. In stage I, susceptible cells are killed en masse by the exposure. In stage II, a small, slow to nongrowing population survives antibiotic exposure that does not exhibit significantly increased resistance according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 55 publications
0
42
0
Order By: Relevance
“…26 These two identified proteins were not located in any of our suggested high variability regions in PA; however, they may be associated with the variation candidates we discovered in this study since some of them showed a close relationship with signal transduction and energy-related pathways.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…26 These two identified proteins were not located in any of our suggested high variability regions in PA; however, they may be associated with the variation candidates we discovered in this study since some of them showed a close relationship with signal transduction and energy-related pathways.…”
Section: Discussionmentioning
confidence: 79%
“…This idea is supported by the fact that when we used transposons to truncate a single gene in these positions, this increased fitness advantage was eliminated, seemingly because the variants involved in the pathways might act together to develop resistance. Resistance in PA is a multiregulation process involving preexisting cellular pathways 26 and accumulated gene mutations (the results shown in this study). By performing comparative genome analysis with 454 pyrosequencing technology, we found three main potential high variability regions in PA, and from the transposon gene functional assay, we found that the physical locations of the genomic variations impacted the development of ciprofloxacin resistance differently.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations